Characterization of two Achromobacter xylosoxidans isolates from patients with pertussis-like symptoms - Orellana-Peralta, F (2015)
To characterize two Achromobacter xylosoxidans recovered from 2 patients diagnosed with pertussis during a Bordetella pertussis surveillance program.